Analysis Of BOPO, LDR, EPS And ROE Ratios To Stock Prices In 10 Major Banks Listed On The IDX - Norma Yuliyanti (Publikasi Indonesia, 2023)
Shares are an investment in the mass market that is quite easy to do nowadays. It is not surprising that even though the Covid-19 pandemic occurred some time ago, the capital market is increasingly busy, both for investment and trading purposes. With the ease of registering as an investor through registered securities, which can be done by downloading the application and attending a basic capital market school with very minimal capital, it is very affordable for novice investors, both among students who already have a KTP (Resident Identification Card) and other people. adults who have income or not. Don't forget that bank issuers have also increased, especially in terms of share prices. This research aims to identify the influence of the operating expense/operating income ratio (BOPO), loan to deposit ratio (LDR), earnings per share (EPS), and return on equity (ROE) on bank share prices. The data in this research was collected from the Indonesian Stock Exchange and the Financial Services Authority.